Islet cell dysfunction in patients with chronic pancreatitis - Roy, Ayan (World J Diabetes, 2020)
Chronic pancreatitis (CP) is characterized by progressive inflammation and fibrosis of the pancreas that eventually leads to pancreatic exocrine and endocrine insufficiency. Diabetes in the background of CP is very difficult to manage due to high glycemic variability and concomitant malabsorption. Progressive beta cell loss leading to insulin deficiency is the cardinal mechanism underlying diabetes development in CP. Alpha cell dysfunction leading to deranged glucagon secretion has been described in different studies using a variety of stimuli in CP. However, the emerging evidence is varied probably because of dependence on the study procedure, the study population as well as on the stage of the disease. The mechanism behind islet cell dysfunction in CP is multifactorial. The intra-islet alpha and beta cell regulation of each other is often lost. Moreover, secretion of the incretin hormones such as glucagon like peptide-1 and glucose-dependent insulinotropic polypeptide is dysregulated. This significantly contributes to islet cell disturbances. Persistent and progressive inflammation with changes in the function of other cells such as islet delta cells and pancreatic polypeptide cells are also implicated in CP. In addition, the different surgical procedures performed in patients with CP and antihyperglycemic drugs used to treat diabetes associated with CP also affect islet cell function. Hence, different factors such as chronic inflammation, dysregulated incretin axis, surgical interventions and anti-diabetic drugs all affect islet cell function in patients with CP. Newer therapies targeting alpha cell function and beta cell regeneration would be useful in the management of pancreatic diabetes in the near future.